2014
DOI: 10.1002/ejoc.201402666
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of α‐Alkylidene β‐Oxo Amides by Palladium‐Catalyzed Carbonylation

Abstract: A direct method to obtain α‐alkylidene β‐oxo amides by the palladium‐catalyzed carbonylation of α‐chloro ketones in the presence of aromatic imines has been described. The methodology can be applied to a variety of C‐aryl imines bearing N‐aryl or N‐alkyl substituents. The entire process is highly stereoselective and affords the α‐alkylidene β‐oxo amides only as (Z) isomers. A mechanistic hypothesis involving an acyl‐β‐lactam intermediate has also been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…imine in dichloromethane in the presence of MgSO 4 . 55 The spectroscopic data of (E)-5c-e, 56 (E)-5h-j, 57 (E)-5f, 58 (E)-5g, 59 (E)-5k, 60 (E)-5l, 61 and (E)-5m 47 are in accordance with reported values.…”
Section: Syn Thesissupporting
confidence: 88%
“…imine in dichloromethane in the presence of MgSO 4 . 55 The spectroscopic data of (E)-5c-e, 56 (E)-5h-j, 57 (E)-5f, 58 (E)-5g, 59 (E)-5k, 60 (E)-5l, 61 and (E)-5m 47 are in accordance with reported values.…”
Section: Syn Thesissupporting
confidence: 88%
“…Indeed, other recent studies have shown similar results when using tris (3,5‐bis(trifluoromethyl)phenyl)borane in imine reductions with good yields being reported . Expansion of the substrate scope required a library of imines, which were readily synthesized using literature procedures . Hydroboration of these various imines was readily achieved, featuring aryl groups substituted with alkyl, fused aryl, electron withdrawing‐ and donating‐groups, as well as variance on the nitrogen atom (Scheme ).…”
Section: Methodsmentioning
confidence: 65%
“…Trapping of proposed key intermediate with benzaldehyde yields nitrone(NI) in the absence of proton donor ( 1 HNMR spectrum in S9) and imine(IM) in the presence of proton donor ( 1 HNMR spectrum in S10) in significant amounts, shown in Scheme . The nitrone is most probably obtained through the attack of proposed intermediate on benzaldehyde and the imine may be obtained by the further reduction of the nitrone.…”
Section: Resultsmentioning
confidence: 99%